Production of 3-hydroxypropionate-containing polymers by engineered C necator H16 - McGregor, Callum (2021)
Alternative materials are needed to replace traditional plastics, since their production and recalcitrance in nature have negative effects on the environment. Polyhydroxyalkanoates (PHAs) are bacterially synthesised polymers which are potential alternatives to plastic on account of their availability from renewable sources, plastic-like properties and biodegradability.